Knowledge mapping of research data management: Uncovering themes and developments through co-occurrence and bibliometric analysis - Ismail, Mohd Ikhwan; Abrizah, A.; Samsuddin, Samsul Farid (Record and Library Journal, 2025)
Background of the study: Discussions on RDM have grown rapidly in scholarly platforms, emerging as a key topic within library and information science (LIS). While existing studies have reviewed and analyzed RDM literature, their scope is often limited to specific areas or timeframes. It is necessary for a detailed and current analysis of RDM literature, providing deeper insights into its complexities, evolution, and future directions. Purpose: The study presents mapping knowledge domains as a method to uncover the thematic landscape, identify significant clusters, and provide a structured understanding of interconnected concepts within the field of RDM. Method: Data were retrieved from Elsevier’s Scopus database as of August 2023. The study conducts bibliometric analysis to examine geographical distribution, publication outlet, authorship trends, and performance metrics within the field. Findings: The dataset spans from 1977 to 2023, with an increase in publications exceeding ten per year from 2012 onwards, amounting to 684 documents in various languages and reference types. The study identifies four research clusters derived from these documents, highlighting key themes namely, RDM services, data sharing, information systems, and data management. Conclusion: The findings underscore the growth of RDM-related research and contribute to a deeper understanding of the underlying structure of RDM, for researchers, practitioners, and policymakers, enabling them to address current challenges and anticipate future developments in this rapidly evolving field.